Perspective on Landfalling Frequency and Genesis Location Variations of Southern China Typhoon During Peak Summer. Issue 12 (17th June 2019) - Zhang, Chengyang; Hu, Chundi; Huang, Gang; Yao, Cai; Zheng, Zhihai; Wang, Teng; Wu, Zeming; Yang, Song; Chen, Dake
Abstract: Increasing intense landfalling typhoons (LFTYs) are of great coastal threatens to southern China. However, changes in genesis location and landfalling frequency of western North Pacific (WNP) LFTY dedicated to southern China remain unclear. Here we identified such LFTYs during peak summer and found that most LFTYs formed south of 20°N and the LFTY genesis locations over southern WNP have also experienced a sharp interdecadal shift since 1998, which are mainly attributed to the large‐scale environment changes induced by the Mega‐La Niña‐like climate shift. However, LFTY frequency (= "landfalling frequency of southern China typhoon") shows a slight increasing trend but without significant interdecadal variation. Variations of LFTY frequency are mainly affected by the easterly steering flows near 20°N over the South China Sea and the Philippine Sea, which are closely linked to the WNP subtropical high activity. Our results provide a new perspective on the LFTY activities dedicated to southern China. Plain Language Summary: We explore the changes in frequency and genesis location of landfalling typhoon (LFTY) dedicated to southern China during peak summer over 1979–2015, which is important for people's life and property from the coastal risk perspective. Results show that the LFTY genesis location is primarily modulated by the Pacific interdecadal variation via modifying the large‐scale atmospheric and oceanic responses over the western North Pacific. While the LFTY frequency (= "landfalling frequency of southern China typhoon") is significantly affected by the easterly steering flows near 20°N over the South China Sea and the Philippine Sea, which are closely linked to the western North Pacific subtropical high activity. Key Points: Landfalling frequency and genesis location of southern China typhoon are affected by different mechanisms during peak summer Interdecadal changes in landfalling typhoon (LFTY) genesis location are primarily attributed to the late‐1990s Mega‐La Niña‐like regime shift Variations of LFTY frequency are mainly driven by the easterly steering flows near 20°N associated with the western North Pacific subtropical high activity